Shift work of nursing professionals and blood pressure, burnout and common mental disorders - Jaqueline Oliveira Valdeviño Nascimento; Juliano dos Santos; Karina Cardoso Meira; Angela Maria Geraldo Pierin; Juliana Nery Souza-Talarico
ABSTRACT Objective: To analyze the influence of shift work on blood pressure, the presence of burnout and common mental disorders in nursing professionals. Method: A cross-sectional study. Burnout was assessed by the Maslach Burnout Inventory, and Common Mental Disorders by the Self-Reporting Questionnaire. Casual blood pressure measurement and Ambulatory Blood Pressure Monitoring (ABPM) were performed. Results: 231 professionals participated. The majority (59.7%) worked in shifts, and this condition was associated (p≤0.05) with: higher weekly workload; doing the night shift; shorter training and work time at the institution; alcoholism; leisure activity; and alteration in ambulatory blood pressure monitoring of the sleep period. The professionals with common mental disorders and who worked in shifts had lower casual diastolic pressure levels (p = 0.039) and higher hypertension prevalence (p = 0.045). The presence of emotional exhaustion was associated with normal waking blood pressure and depersonalization with altered sleep blood pressure. Conclusion: Shift work was associated with a higher prevalence of work-related negative factors, inadequate habits and lifestyles, and change in sleep blood pressure.